2021
DOI: 10.1021/acssuschemeng.1c01705
|View full text |Cite
|
Sign up to set email alerts
|

Novel Extraction Process for Gold Recovery from Thiosulfate Solution Using Phosphonium Ionic Liquids

Abstract: A novel and sustainable technology to recover gold from thiosulfate medium using ionic liquids, i.e., Cyphos IL 101 (Cy IL 101) and Cyphos IL 102 (Cy IL 102) diluted in toluene, has been developed. Gold was extracted into the ionic liquid phase as [{P66614 +}3{Au­(S2O3)2 3–}] and stripped using NaCl solution. The recyclability of ionic liquids has shown promising recirculation of the solvents for the extraction of gold from thiosulfate medium. Gold was quantitatively extracted from 0.2 mol/L sodium thiosulfate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 37 publications
0
34
0
Order By: Relevance
“…Cyphos 101 in toluene is an efficient extractant for gold(III) from thiosulfate solutions, with an extraction efficiency of 99% [31]; undiluted Cyphos 101 provides quantitative recovery of platinum(IV) and palladium(II) from a leaching acidic solution of waste catalytic converters [32].…”
Section: Ionic Liquids Based On Phosphonium Cations For Metal Extractionmentioning
confidence: 99%
“…Cyphos 101 in toluene is an efficient extractant for gold(III) from thiosulfate solutions, with an extraction efficiency of 99% [31]; undiluted Cyphos 101 provides quantitative recovery of platinum(IV) and palladium(II) from a leaching acidic solution of waste catalytic converters [32].…”
Section: Ionic Liquids Based On Phosphonium Cations For Metal Extractionmentioning
confidence: 99%
“…The loading capacity depends on the specific surface area and pore structure of the activated carbon; however, adsorption rate is dependent upon the particle size and specific surface area of the activated carbon, mixing efficiency, and pulp density . Gold adsorption rates in CIP and CIL operations are usually very low, and the gold loading capacity in CIP and CIL operations is far below the equibrilim capacity of the activated carbon. , In order to effectively separate the loaded activated carbon from the slurry by screening, the activated carbon used in the operations has to be coarse particles (diameter = 1.0–3.0 mm), and the adsorption rate of the activated carbon decreases significantly with the increase of the particle size because the mean pore length increases. , Thus, the adsorption rate of activated carbon used in the current mining process is mainly limited by the particle size, even though, there is still much gold left and fine carbon particles that cannot be recovered. , …”
Section: Introductionmentioning
confidence: 99%
“…13,17 Thus, the adsorption rate of activated carbon used in the current mining process is mainly limited by the particle size, even though, there is still much gold left and fine carbon particles that cannot be recovered. 18,19 There have been some developments on activated carbon for aurocyanide recovery in the past decade. Poinern et al 15 investigated the use of macadamia nut based granular activated carbon for aurocyanide adsorption, and discovered that the gold loading capacity of this activated carbon is comparable to the commercial coconut-shell-based activated carbon.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Kejun et al extracted Au­(I) from thiosulfate solutions with trioctylmethylammonium chloride, which is the main component of Aliquat 336, dissolved in a mixture of n -octane and 1-hexanol . Mahandra et al reported on the use of ionic liquids such as Cyphos IL 101 and Cyphos IL 102 for the sustainable recovery of Au­(I) from thiosulfate solutions . Mowafy and Mohamed extracted Au­(III) from hydrochloric acid solutions with long-chain monoamides in aromatic and aliphatic diluents.…”
Section: Introductionmentioning
confidence: 99%
“…1 Mahandra et al reported on the use of ionic liquids such as Cyphos IL 101 and Cyphos IL 102 for the sustainable recovery of Au(I) from thiosulfate solutions. 2 Mowafy and Mohamed 3 extracted Au(III) from hydrochloric acid solutions with long-chain monoamides in aromatic and aliphatic diluents. Oshima et al reported on the successful extraction of Au(III) from hydrochloric acid solutions using aromatic ethers 4 and ketone compounds, 5 while Salvadóet al 6 demonstrated the suitability of tri-isobutyl phosphine sulfide in toluene.…”
Section: ■ Introductionmentioning
confidence: 99%